Actions of Their Own to Learn Studies in Knowing, Acting, and Being - Shapiro, Bonnie (Brill, 2017)
What does it mean to take actions of one's own to learn? How do human beings create meaning for themselves and with others? How can learners' active efforts to build knowledge be encouraged and supported? In this edited compilation, scholars from a diverse range of academic and professional backgrounds address these questions, grounded in the conviction that the ability to take effective action of one's own to learn is itself an essential form of knowledge. In an era of dramatic social, environmental and political change, the need to access vast amounts of information to make decisions demands that learners become active agents in their own knowledge development. Educators are transforming ideas about their role(s) as they strive to provide guidance to help learners take the lead in their own learning. Learners are building new ideas about their capacities to gather and organize information while working with others. No longer simply consumers of information, they are beginning to see themselves as capable and effective researchers. Researchers are also expanding ideas about their knowledge-gathering work and identities. No longer simply reporters of information, researchers are seeing themselves as learners, as they engage in deeper, more collaborative ways with participants in their research. Chapter authors describe their dedicated, and often career long journeys to show the vital connections between knowledge, acting to learn, identity and being. To engage in this work means disrupting traditional ideas about how knowledge is most effectively acquired. This book will inspire researchers, educators and educational planners as they build the kinds of new participative structures needed to support individual and collective actions to learn.